Gerakan Sayang Ibu Sebagai Upaya “Making Pregnancy Safer” Masa Pandemi Covid-19 Di Kabupaten Aceh Barat - Teungku Nih Farisni; Yarmaliza Yarmaliza; Fitriani Fitriani; Fitrah Reynaldi; Zakiyuddin Zakiyuddin; Venni Nella Syahputri (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
The results of the 2018 Basic Health Research (Riskesdas) showed that only 25.2% of pregnant women received additional food, while the rest did not receive supplementary food (PMT) of 74.8%. This situation in the short term affects the nutritional status of pregnant women and in the long term becomes a risk factor for complications of pregnancy and childbirth, the risk of maternal death, the rate of prematurity, low birth weight and perinatal mortality and the incidence of stunting in children. Maternal love movement (GSI) is a very appropriate method in maintaining the health of pregnant women so that the nutritional problems of pregnant women can be overcome. GSI will be driven by village midwives, PKK women, posyandu cadres and village officials. In this GSI forum, village midwives, PKK women, posyandu cadres and gampong apparatus will meet regularly every 2 (two) weeks or at least once a month including home visits to pregnant women to provide education, discuss and provide mutual support related to maternal health. pregnancy and the fulfillment of balanced nutrition during pregnancy. The results of this service are the formation of GSI which is able to empower pregnant women so that they can increase their knowledge and skills in maintaining health during pregnancy and the fulfillment of balanced nutrition that can be obtained in the area where they live, GSI as a sustainable counselor in the village, and decreasing cases of anemia and Chronic energy deficiency in pregnant women in the coastal area of ​​West Aceh Regency.